Comparing EWGSOP2 and FNIH Sarcopenia Definitions: Agreement and 3-Year Survival Prognostic Value in Older Hospitalized Adults: The GLISTEN Study. (19th October 2019) - Bianchi, Lara; Maietti, Elisa; Abete, Pasquale; Bellelli, Giuseppe; Bo, Mario; Cherubini, Antonio; Corica, Francesco; Di Bari, Mauro; Maggio, Marcello; Martone, Anna Maria; Rizzo, Maria Rosaria; Rossi, Andrea P; et al.
Abstract: Background: Sarcopenia is common among older hospitalized adults but estimates vary according to definitions used. Aims of this study were to investigate the agreement between the European Working Group on Sarcopenia in Older People (EWGSOP2) and the Foundation for the National Institutes of Health (FNIH) Sarcopenia Project criteria and to compare the predictive value of both definitions for 3-year mortality. Methods: Analysis was performed on 610 older hospitalized patients enrolled in the GLISTEN study. Participants were categorized as sarcopenic or not sarcopenic according to EWGSOP2 and FNIH definitions separately and in a four-group variable (neither criterion positive, only EWGSOP2, only FNIH, and both criteria). Results: Sarcopenia prevalence was 22.8% and 23.9% using EWGSOP2 and FNIH criteria, respectively, with a low classification agreement (Cohen's kappa statistic: 0.29). Sarcopenic participants by each definitions had higher mortality rate when compared to those not sarcopenic (both log-rank test: p < .001). Participants who met both positive criteria had the shorter survival as compared with the other three groups. Cox models showed that, after adjustment for potential confounders, only EWGSOP2 definition predicted 3-year mortality (hazard ratio [HR] 1.84; 95% confidence interval [CI] 1.33–2.57). When the four-group variable was used, compared with the NO EWGSOP2/NO FNIH group, significant mortality risk was found for the EWGSOP2 (HR 2.08; 95% CI 1.38–3.16) and the combined EWGSOP2/FNIH group (HR 1.75; 95% CI 1.11–2.79). Conclusions: Agreement between EWGSOP2 and FNIH definitions is poor. Sarcopenia on hospital admission is associated with increased risk of 3-year mortality and EWGSOP2 criteria seem to have the highest predictive value.